Wolfberries potentiate mitophagy and enhance mitochondrial biogenesis leading to prevention of hepatic steatosis in obese mice: The role of AMP‐activated protein kinase α2 subunit. Issue 5 (22nd January 2014) - Lin, Dingbo; He, Hui; Ji, Hua; Willis, Jordan; Willard, Lloyd; Jiang, Yu; Medeiros, Denis M.; Wark, Logan; Han, Jing; Liu, Yongzhang; Lu, Bin
<x xml:space="preserve">Abstract</x> Scope The aim of this study is to investigate whether AMP‐activated protein kinase α2 (AMPKα2) is essential for wolfberry's protective effects on mitochondrial dysfunction and subsequent hepatic steatosis in mice. Methods and results Six‐week‐old male AMPKα2 knockout mice and genetic background C57BL/6J (B6) mice were fed a control, high‐fat diet (HD, 45% (kilocalorie) fat), and/or HD with 5% (kilocalarie) wolfberry diets for 18 wk. At termination, blood and liver tissues were sampled for analysis by ELISA, HPLC, microscopy, real‐time PCR, and Western blot. HD lowered hepatic lutein and zeaxanthin contents, inhibited protein expression of β, β‐carotene 9′, 10′‐oxygenase 2 (BCO2) and heat shock protein 60 in mitochondria, increased reactive oxygen species level, and suppressed mitophagy and mitochondrial biogenesis as determined by accumulation of p62, inhibited phosphorylation of Unc‐51‐like kinase 1 on Ser555, and declined expression of peroxisome proliferator‐activated receptor γ coactivator 1 α, resulting in hepatic steatosis in B6 and knockout mice. Dietary wolfberry elevated the xanthophyll concentrations and enhanced expression of BCO2 and heat shock protein 60, attenuated mitochondrial oxidative stress, activated AMPKα2, potentiated mitophagy and mitochondrial biogenesis, and enhanced lipid oxidation and secretion in the liver of B6 mice. Conclusion Dietary wolfberry selectively activated AMPKα2, which resulted in enhanced mitochondrial biogenesis and potentiated mitophagy, leading to the prevention of hepatic steatosis in obese mice.